3x+8=-27-2x

Simple and best practice solution for 3x+8=-27-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+8=-27-2x equation:


Simplifying
3x + 8 = -27 + -2x

Reorder the terms:
8 + 3x = -27 + -2x

Solving
8 + 3x = -27 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
8 + 3x + 2x = -27 + -2x + 2x

Combine like terms: 3x + 2x = 5x
8 + 5x = -27 + -2x + 2x

Combine like terms: -2x + 2x = 0
8 + 5x = -27 + 0
8 + 5x = -27

Add '-8' to each side of the equation.
8 + -8 + 5x = -27 + -8

Combine like terms: 8 + -8 = 0
0 + 5x = -27 + -8
5x = -27 + -8

Combine like terms: -27 + -8 = -35
5x = -35

Divide each side by '5'.
x = -7

Simplifying
x = -7

See similar equations:

| g-500=225+g | | 2x+3x+4x-5=22+3+4x | | 2(2)-y=6 | | 7+4x=10+x | | 7n+18=6n+(n-9) | | x+3/4=4 | | 117=4(x+45)+3x | | 1.02g-5=0.61 | | 21y=31.64 | | x+3/4=3/4+x+4 | | 13=7+3s | | 2a^2+11a-63= | | 4+5r=-11 | | 2x/3-3x/5=2 | | 6x-4=2+4x | | x+3+2x+4=x+3+x+6 | | 5-7x/6=3/2 | | 3(x-6)=2(x+7) | | -f(6)=45+10x | | 6x-12=8x+5 | | -11+y=8 | | 6(2-(2x-4))=2(-3-3x) | | 5+2d=9 | | 17-4d=5 | | -5(2t-5)+8t=5t-8 | | 3x^2-45x+70=0 | | -2x=-4(-3)-4 | | 4w+3=-25 | | -2x=-4(-3)3-4 | | 4.6=-7+x | | -2x=-4-3-4 | | -f(x)=45+10x |

Equations solver categories